Social comparisons in oligopsony - Laszlo Goerke; Michael Neugart (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2017)
A large body of evidence suggests that social comparisons matter for workers' valuation of the wage they receive. The consequences of social comparisons in imperfectly competitive labor markets are less well understood. We analyze an oligopsonistic model of the labor market where workers derive (dis-) utility from comparing their own wage with wages paid at other firms. As social comparisons become more preva lent all workers are paid higher wages, the wage distribution becomes more equal, and employment shifts to high productivity firms. Moreover, the total wage bill and output increase, while aggregate profits decline. Overall welfare rises. Our theoretical results have implications for estimating the elasticity of the labor supply curve facing a firm.
Keywords: D62; J22; J42; 330; social comparisons; status seeking; oligopsony; wage distribution; functional income distribution; welfare